Formação Universitária e Educação Popular: convergências com a Espiritualidade a partir de vivências estudantis na exensão. - Barreto, Betânia Maria Vilas Bôas (2013)
This research aimed to comprehend the meaning of spirituality in university education practices directed to Popular Education, through the experience study of the Popular Education Project and Family Health Care (PEPFHC) of Federal University of Paraíba, anextension interdisciplinary university project which accompanies the residents and social movements of the João Pessoa outskirts. The interest and approximation at this set of themes were developed from concerns and researches along the professor career, unsatisfied with the academic practices almost exclusively focused on technical and scientific knowledge teachings and in logical rationality, devaluing the subjective dimensions inherent on the professional acting. These researches and studies were approximating of contemporary discussions on spiruality and on the importance of its valorization for overcoming limits of classical modern rationality. The spirituality is known as a search process of most fundamental motivations and feelings for existence, in which Paulo Freire denominate search of being more present in all people . This process is highly present in university education, nevertheless it is unappreciated in most of its educational practices. However some university initiatives pointed by Popular Education have been valuing the spiritual dimension. The PEPFHC is one of theses initiatives. Your fifteen year duration , the participation of hundreds of students in successive classes, the involvement of different department professors and the achievement of various studies and publications consolidated a pedagogical identity and an institutional acceptance, making this experience much profitable for this study. It was took as focus a spiritual transformation process of he students, in their searches for being better and find the most fundamental senses and motivations for their professional and personal lives, along their participation on the Project. It is about a qualitative study which used, as technique of data collecting, the participant observation and the set of ten testimonies of students related to its experiences on the Project, included on the book of the Project published in 2011. The participant observation occurred on the period from april 2010 to may 2011. From then on, adialetic analysis was developed to interpretation of data, observing the vivid processes and the transformations occurred on students, their significant learnings, as well as the contradictions and limits of the experiences on the Project. Five significant dimensions were identified of the experiences, corresponding to phases of development of the spiritual transformation of the students. It was realized that the most important spiritual transformation happens from amorous linkage which students develop with residents, families and movements from this outskirt community. The reception, valorization and discussion subjective concerns, provoked by the involvements of the students in care actions and in political communitarian fight, through the pedagogic dynamics of the Project, showed to be fundamental for a greater elaboration and reach of these transformations. It was noticed the importance and innovation of the theoretical-methodological proposal of the PEPFHC, under the perspective of Popular Education, as a space to a spiritual elaboration for the students. In this pedagogy, a new scientific knowledge interconnected with the spiritual dimensions of the students, as a way of knowledge construction on the academy and new alternatives for a university education more humane and transformed.